Sword of the Spirit, Shield of Faith: Religion in American War and Diplomacy. - Inboden, William (Fides et historia, 2012)
The article reviews the book ''Sword of the Spirit, Shield of Faith: Religion in American War and Diplomacy,'' by Andrew Preston.